2013
DOI: 10.1007/s11126-013-9257-3
|View full text |Cite
|
Sign up to set email alerts
|

Affective Temperaments in Alcohol and Opiate Addictions

Abstract: Temperament is considered as a biological disposition reflected by relatively stable features related to mood and reactivity to external and internal stimuli, including variability in emotional reactions. The aim of the present study is to test the hypothesis that affective temperaments might differ according to co-occurring mood disorders among patients with alcohol and/or opiate dependence; to explore the relationship between temperaments and dual substance use disorders (SUDs, alcohol and other drugs). Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…This approach, which focuses on validated genetic variants, as opposed to comprehensive next-generation sequencing, is the preferred approach of many in the field 26. The phenotypic factors tested include age (whether or not they were 16–45 years old),27,28 personal history of alcohol abuse,23,29 personal history of illegal drug abuse,8,30 personal history of prescription drug abuse,31 and personal history of other mental health diseases including attention deficit disorder,32 obsessive compulsive disorder,33 bipolar disorder,24 and schizophrenia 34…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach, which focuses on validated genetic variants, as opposed to comprehensive next-generation sequencing, is the preferred approach of many in the field 26. The phenotypic factors tested include age (whether or not they were 16–45 years old),27,28 personal history of alcohol abuse,23,29 personal history of illegal drug abuse,8,30 personal history of prescription drug abuse,31 and personal history of other mental health diseases including attention deficit disorder,32 obsessive compulsive disorder,33 bipolar disorder,24 and schizophrenia 34…”
Section: Methodsmentioning
confidence: 99%
“…The Proove Opioid Risk (POR) profile is a panel test that combines known phenotypic risk factors with validated genetic markers in a patented algorithm to predict risk of OUD with a high degree of sensitivity. The interplay between environment and genetics is widely acknowledged 12,23,24. Therefore, an evaluation of both phenotypic and genetic risk is necessary to achieve predictive accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[26]. Many studies have reported a relationship between temperaments and mental problems (e.g., suicide) [27, 28], mental status in non-clinical populations [29], depressive symptoms [3032], mood disorders [3337], anxiety disorders [38], alcohol abuse or dependence [39, 40], and substance abuse [41, 42]. In the workplace, a depressive temperament has been reported to be a kind of work-oriented personality [43], hyperthymic temperament has been reported to be a type of hyper-adapted personality [44].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of affective temperaments is clinically useful not only in the case of mood disorders but also in patients with rheumatoid arthritis (Rezvani et al, 2014), obesity (Amann et al, 2009), HIV ) and alcohol and/or opiate dependence (Khazaal et al, 2013). We believe that it is important that affective temperaments encompass healthy personality traits (Rovai et al, 2013) and have both universal and culturally specific characteristics, as proposed by Vázquez, Tondo, Mazzarini, and Gonda (2012).…”
Section: Introductionmentioning
confidence: 96%